Race, Socioeconomic Status, and Cerebellum Cortex Fractional Anisotropy in Pre-Adolescents - Shervin Assari; Shanika Boyce (MDPI AG, 2021)
Introduction: Cerebellum cortex fractional anisotropy is a proxy of the integrity of the cerebellum cortex. However, less is known about how it is shaped by race and socioeconomic status (SES) indicators such as parental education and household income. Purpose: In a national sample of American pre-adolescents, this study had two aims: to test the effects of two SES indicators, namely parental education and household income, on cerebellum cortex fractional anisotropy, and to explore racial differences in these effects. Methods: Using data from the Adolescent Brain Cognitive Development (ABCD) study, we analyzed the diffusion Magnetic Resonance Imaging (dMRI) data of 9565, 9-10-year-old pre-adolescents. The main outcomes were cerebellum cortex fractional anisotropy separately calculated for right and left hemispheres using dMRI. The independent variables were parental education and household income; both treated as categorical variables. Age, sex, ethnicity, and family marital status were the covariates. Race was the moderator. To analyze the data, we used mixed-effects regression models without and with interaction terms. We controlled for propensity score and MRI device. Results: High parental education and household income were associated with lower right and left cerebellum cortex fractional anisotropy. In the pooled sample, we found significant interactions between race and parental education and household income, suggesting that the effects of parental education and household income on the right and left cerebellum cortex fractional anisotropy are all significantly larger for White than for Black pre-adolescents. Conclusions: The effects of SES indicators, namely parental education and household income, on pre-adolescents' cerebellum cortex microstructure and integrity are weaker in Black than in White families. This finding is in line with the Marginalization-related Diminished Returns (MDRs), defined as weaker effects of SES indicators for Blacks and other racial and minority groups than for Whites.